The Analysis Patriarchy an Feminism of Katherine in The Taming of Shrew - Anjani, Silvia (Universitas PGRI Yogyakarta, 2024)
This research aims to explain the main female character and the social circumstances experienced by the main character in the play The Taming of the Shrew. The main female character is Katherine, a woman full of courage and strength to fight against the circumstances that occur in the environment. The data used comes from the text of the play The Taming of Shrew and additional data from several articles and books related to the topic. The researcher also used a descriptive method to explain the data that has been researched sourced from the text of the play The Taming of Shrew and additional data from several articles and books. The results found that with this method, it was concluded that there were things that happened such as patriarchy, feminism and gender experienced by Katherine in the play. William Shakespeare portrayed the character of Katherine in an indirect way. The main character is perfectly portrayed as a woman in the struggle against patriarchy and gender through her feminism movement. William Shakespeare portrays the character of Katherine indirectly and creates an environment that criticises the patriarchal system and through Katherine can blind women to the feminist movement without fear. The social phenomena of patriarchy, gender, and feminism are inseparable from William Shakespeare's time to the modern day.